Numerical treatment of partial differential equations - Roos Hans-Gorg; Stynes Martin (Berlin Springer-Verlag, 2007)
This book deals with discretization techniques for elliptic, parabolic and hyperbolic partial differential equations. It provides an introduction to the main principles of discretizations and presents to the reader the ideas and analysis of advanced nume
Keywords: Differential equations-numerical solutions; Finite differences; Finite element method; Numerical analysis